Pedagogical cognitive knowledge in an effort to improve students' cognitive abilities: Systematic literature review - Fitri Rahmadhani; Aldeva Ilhami; Yuni Ernika Saputri (Jurnal JPSD (Jurnal Pendidikan Sekolah Dasar), 2022)
This researcher aims to improve pedagogical cognitive knowledge in an effort to improve students' cognitive abilities. This research method is the SLR (Systematic Literature Review) method. So that the selected literature is relevant search using the keywords "PCK, Cognitive Ability, and SMP. Furthermore, screening is carried out to get scientific article publications from 2017-2022 which discuss pedagogical content knowledge improve cognitive abilities. The results showed that there were 13 articles worth analyzing. The results showed that Pedagogical Cognitive Knowledge has an effect on increasing students' cognitive abilities